2018
DOI: 10.3390/jcs2020025
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Graphene Oxide: Effect of Reduction on Electrical Conductivity

Abstract: In this study, the effect of reduction on the electrical conductivity of Graphene Oxide (GO) is investigated. The aim of this fabrication was to render electromagnetic interference (EMI) shielding to thin polymer films using GO as fillers. The electrical conductivity was determined using the four-probe method and shielding effectiveness was theoretically determined using the experimentally obtained conductivity values. The initial oxidation of graphite was performed using Hummers' method and the oxidized GO wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 34 publications
4
39
1
Order By: Relevance
“…The only outlier was the F-GO/GCE, as it accounted for only 28.33% of the GO detection signal. However, it is known that fluorine doping completely disrupts the sp2 carbon ring structure, thus further decreasing the conductivity of GO [13]. In comparison, nitrogen or boron-doped graphene oxide typically possessed heteroatoms that replaced the carbon atoms, and became incorporated within the ring structures [39].…”
Section: Electrochemical Behaviors Of Naproxen At the Modified Electrmentioning
confidence: 99%
See 2 more Smart Citations
“…The only outlier was the F-GO/GCE, as it accounted for only 28.33% of the GO detection signal. However, it is known that fluorine doping completely disrupts the sp2 carbon ring structure, thus further decreasing the conductivity of GO [13]. In comparison, nitrogen or boron-doped graphene oxide typically possessed heteroatoms that replaced the carbon atoms, and became incorporated within the ring structures [39].…”
Section: Electrochemical Behaviors Of Naproxen At the Modified Electrmentioning
confidence: 99%
“…Hendawy et al reported nanomaterial-based carbon paste electrodes for the detection of naproxen and its degradation product [10]. Over the last decade, the exploration of graphene and graphene-based nanomaterials has garnered tremendous attention due to their unique electronic, structural, and physical attributes [11][12][13][14]. The structure of graphene includes a single layer of sp2-hybridized hexagonal lattices that form honeycomb structures with a high surface area, which are both electronically and thermally conductive [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure a, the electrical conductivity of the as‐prepared 22 μm thick TaS 2 HA 0.371 NMF 0.135 foil was measured to be 1173.8 S cm −1 , which is among the best values in solution‐based graphene and IGAs, such as graphene films made by vacuum filtration (≈(0.8–3) × 10 2 S cm −1 ), inkjet printing (2.5 × 10 2 S cm −1 ), and casting ((3.3–5.4) × 10 2 S cm −1 ), and a conducting hydric TiS 2 foil synthesized by hydrogen intercalation (6.8 × 10 2 S cm −1 ) . Thus, the as‐prepared hybrid foil shows great potential to be incorporated into flexible electrodes of high conductivity.…”
mentioning
confidence: 94%
“…The foil shows excellent mechanical stability and chemical stability in air. A high electrical conductivity and high electromagnetic interference (EMI) shielding effectiveness (SE) values were observed, which are among the best values for solution‐based thin‐film graphene or IGAs . The solution‐based strategy used to fabricate high‐quality, large‐area flexible foil of TMDC/organic superlattices could provide new opportunities for electronic devices that rely on the abnormal properties of 2D materials.…”
mentioning
confidence: 99%